Effect of Irrigation Standards and Periods on the Development Phases and Vegetation Period of Say "Uzbek6" Variety (Eurasian Journal of Research, Development and Innovation, 2023)
This article presents the impact of the irrigation regime on the growth and development of the Uzbek-6 soybean variety and the growing season. In the experiment with a soil moisture content of 65-70-65% before irrigation compared to the FPV, the full ripening period of the variety was observed on September 1, and the growing season was 138 days. In this variant, soil moisture before watering is low compared to other variants, and the length of the day between waterings is the reason for the acceleration of the full ripening of the plant. With a soil moisture content of 80-80-70% compared to the FPV, the full ripening period of the variety was observed on September 5, the growing season was 142 days, it is proved that high soil moisture causes the growing season, the plant is extended by 4-5 days.